Impact of the updated hemodynamic definitions on diagnosis rates of pulmonary hypertension. (August 2020) - Tanyeri, Seda; Akbal, Ozgur Y.; Keskin, Berhan; Hakgor, Aykun; Karagoz, Ali; Tokgoz, Hacer Ceren; Dogan, Cem; Bayram, Zubeyde; Kulahcioglu, Seyhmus; Erdogan, Emrah; Balaban, Ismail; Ceneli, Dogancan; et al.
We evaluated whether updated pulmonary hypertension definitive criteria proposed in sixth World Symposium on Pulmonary Hypertension had an impact on diagnosis of overall pulmonary hypertension and pre-capillary and combined pre- and post-capillary phenotypes as compared to those in European Society of Cardiology/European Respiratory Society 2015 pulmonary hypertension Guidelines. Study group comprised the retrospectively evaluated 1300 patients (age 53.1 ± 18.8 years, female 807, 62.1%) who underwent right heart catheterization with different indications between 2006 and 2018. Mean pulmonary arterial pressure ≥25 mmHg (European Society of Cardiology) and PAMP (mean pulmonary arterial pressure) >20 mmHg (World Symposium on Pulmonary Hypertension) right heart catheterization definitions criteria were used, respectively. For pre-capillary pulmonary hypertension, pulmonary artery wedge pressure ≤15 mmHg and pulmonary vascular resistance ≥3 Wood units criteria were included in the both definitions. Normal mean pulmonary arterial pressure (<21 mmHg), borderline mean pulmonary arterial pressure elevation (21–24 mmHg), and overt pulmonary hypertension (≥25 mmHg) were documented in 21.1, 9.8, and 69.1% of the patients, respectively. The pre-capillary and combined pre- and post-capillary pulmonary hypertension were noted in 2.9 and 1.1%, 8.7 and 2.5%, and 34.6 and 36.6% of the patients with normal mean pulmonary arterial pressure, borderline, and overt pulmonary hypertension subgroups, respectively. The World Symposium on Pulmonary Hypertension versus European Society of Cardiology/European Respiratory Society definitions resulted in a net 9.8% increase in the diagnosis of overall pulmonary hypertension whereas increases in the pre-capillary pulmonary hypertension and combined pre- and post-capillary pulmonary hypertension diagnosis were only 0.8 and 0.3%, respectively. The re-definition of mean pulmonary arterial pressure threshold seems to increase the frequency of the overall pulmonary hypertension diagnosis. However, this increase was mainly originated from those in post-capillary pulmonary hypertension subgroup whereas its impact on pre-capillary and combined pre- and post-capillary pulmonary hypertension was negligible. Moreover, criteria of pre-capillary pulmonary vascular disease and combined pre- and post-capillary phenotypes were still detectable even in the presence of normal mean pulmonary arterial pressure. The obligatory criteria of pulmonary vascular resistance ≥3 Wood units seems to keep specificity for discrimination between pre-capillary versus post-C pulmonary hypertension after lowering the definitive mean pulmonary arterial pressure threshold to 20 mmHg.